2008
DOI: 10.1101/gr.7136508
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Pelotomaculum thermopropionicum reveals niche-associated evolution in anaerobic microbiota

Abstract: The anaerobic biodegradation of organic matter is accomplished by sequential syntrophic catabolism by microbes in different niches. Pelotomaculum thermopropionicum is a representative syntrophic bacterium that catalyzes the intermediate bottleneck step in the anaerobic-biodegradation process, whereby volatile fatty acids (VFAs) and alcohols produced by upstream fermenting bacteria are converted to acetate, hydrogen, and carbon dioxide (substrates for downstream methanogenic archaea). To reveal genomic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 43 publications
7
102
0
1
Order By: Relevance
“…These results were consistent with previous phylogenetic approaches that showed high gene sharing between syntrophic organisms (Cordero and Hogeweg, 2009). Additionally, it has been suggested that HGT is responsible for similar codon usage bias between Pelotomaculum thermopropionicum and other syntrophic organisms (Kosaka et al, 2008) and that syntrophic interactions between Desulfovibrio vulgaris and Methanosarcina barkeri had evolved as a result of ancestral HGT (Scholten et al, 2007). In conclusion, the previous syntrophic organisms represent examples of how tight ecological relationships (that is, physiological dependence and physical contact) have favored the transfer of genetic material between distantly related organisms.…”
Section: Resultsmentioning
confidence: 97%
“…These results were consistent with previous phylogenetic approaches that showed high gene sharing between syntrophic organisms (Cordero and Hogeweg, 2009). Additionally, it has been suggested that HGT is responsible for similar codon usage bias between Pelotomaculum thermopropionicum and other syntrophic organisms (Kosaka et al, 2008) and that syntrophic interactions between Desulfovibrio vulgaris and Methanosarcina barkeri had evolved as a result of ancestral HGT (Scholten et al, 2007). In conclusion, the previous syntrophic organisms represent examples of how tight ecological relationships (that is, physiological dependence and physical contact) have favored the transfer of genetic material between distantly related organisms.…”
Section: Resultsmentioning
confidence: 97%
“…YIT12065, is only 82-92% identical to these co-occurring OTUs; very little is known about this isolate's biology. The presence of obligate syntrophs for methanogens in the human gut would not be surprising, because they are known to exist in other environments, such as sludge (39,40).…”
Section: Mz Twins Have Higher Concordance For Gut Methanogens Than Dzmentioning
confidence: 99%
“…Cloacimonetes': syntrophic propionate degraders This ecogenomic effort also generated a pangenome for Atribacteria, another poorly characterized candidate phylum associated with methanogenic environments ) that our previous study could not address. This Atribacteria encodes propionate metabolism and specifically expresses methylmalonyl-CoA pathway genes with high homology (52-71%) to those found in Pelotomaculum thermopropionicum strain SI, a representative thermophilic propionate-degrading syntroph (Supplementary Table S11; Kosaka et al, 2008). For energy-conserving electron disposal, Atribacteria expresses an electron-bifurcating formate dehydrogenase (Wang et al, 2013) and Fd red -dependent energy-conserving membranebound hydrogenase (Figures 2 and 3), suggesting that both formate and H 2 generation may take part in propionate degradation as observed in Syntrophobacter (Harmsen et al, 1998).…”
Section: Hdrabc (Supplementarymentioning
confidence: 99%